Effect of solid state fermentation on nutrient content and ileal amino acids digestibility of canola meal in broiler chickens - Ahmed, Aljuobori; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Abdullah, Norhani; Liang, Juan Boo; Awad, Elmutaz A. (PAGEPress, 2014)
The aim of the current study was to investigate the potential of Lactobacillus salivarius solid state fermentation for reduction of glucosinolate content in canola meal (CM) as well as the improvement of its nutrient digestibility for broiler chickens. Canola meal was treated with the L. salivarius in solid state fermentation for 30 days. Nutrients ileal digestibility was tested using 42-day-old broilers fed by either CM or fermented CM (FCM) as the sole source of energy and protein. The results showed that fermentation of CM using L. salivarius reduced glucosinolate content of CM by 38%. The digestibility coefficient was improved significantly for crude protein, Met, Cys, Arg, Asp, Glu, and Ser in FCM compared to CM. However, apparent metabolisable energy of CM was not affected by fermentation. It appears that fermentation treatment of CM using L. salivarius may improve the overall nutritive value of CM for broiler chickens, reducing its total glucosinolate and crude fibre content by 38 and 16%, respectively.